La cobertura de los medios de comunicación digitales de Babahoyo acerca de la Cultura Montubia de Babahoyo - Espinoza León, Leonela Stefanía (2023)
The present work focuses on the analysis of the coverage of the digital media of Babahoyo on the Montubia culture, currently digital media have become present with new technologies, so its cultural and social dynamics are important. , in this research the selection of two specific media was proposed: AlDIA and El Vocero, during the year 2022. The line of research required was: communication, culture, environment and society, the methodology used was mixed, since it combined quantitative and qualitative, you can obtain detailed and valuable information. For this purpose, an observation sheet and interview were carried out, all of this allowed the resolution of the problem. Many times it may be that content creators do not have enough knowledge about cultural groups, which is why they do not make a fair and accurate representation in their media. The objectives were to identify the current situation of digital media to establish theoretical criteria about the importance and presence of Montubian culture. We also sought to examine the publications of these media, since the Montubios have maintained their practices and customs over several generations and it is of utmost importance that their culture is respected and preserved and there is no loss of cultural identity, once completed. the case study, and through the aforementioned techniques it was possible to verify that there is a low rate of representation of the Montubia culture in digital media.